Thromboelastometric Profile of Sepsis-Induced Coagulopathy and Overt Disseminated Intravascular Coagulation: A Retrospective Cohort Study - Piotr F. Czempik (Journal of Clinical Medicine, 2026)
Background/Objectives: Sepsis may cause hemostatic disturbances. Viscoelastic hemostatic assays, such as rotational thromboelastometry (ROTEM), may reveal functional hemostatic changes not captured by conventional tests. The study aimed to analyze ROTEM parameters in sepsis-induced coagulopathy (SIC) and overt disseminated intravascular coagulation (DIC). Methods: A retrospective cohort analysis of adult ICU patients with sepsis or septic shock (May 2023–August 2026) who had ROTEM testing (minimum EXTEM and FIBTEM) performed was conducted. Clinical scores (SOFA, ISTH SIC, ISTH overt DIC), conventional coagulation tests, inflammatory biomarkers, and full ROTEM panels (INTEM, EXTEM, FIBTEM, APTEM) were retrived. Group comparisons used Kruskal–Wallis and pairwise Wilcoxon tests; associations with ICU mortality were assessed by multivariable logistic regression adjusted for age, sex, and SOFA. Results: Of 167 patients, 40 (23.9%) met ISTH SIC criteria, 24 (14.4%) met overt DIC criteria, and 103 (61.7%) had no SIC/DIC. Patients with SIC or DIC demonstrated slower clot propagation, lower early clot amplitudes and maximal clot firmness, and lower fibrinolytic activity compared to septic patients without coagulopathy. The only ROTEM parameter that differed between SIC and overt DIC was platelet contribution to clot strength, which was lower in DIC compared with the SIC subgroup. In multivariable logistic regression sensitivity analysis, with no SOFA score included as a covariate, no pre-specified ROTEM parameter was associated with ICU mortality after adjustment for age and sex in the current cohort. The coagulopathy subgroup itself was not an independent predictor of ICU death after adjustment. Conclusions: Rotational thromboelastometry shows distinct features in patients with SIC and sepsis-induced overt DIC compared with patients without coagulopathy. In the current cohort, the only ROTEM parameter that distinguished overt DIC from SIC was PLT contribution to clot strength. No ROTEM parameter was associated with short-term mortality in the presented cohort.